ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERINVESTASI GENERASI Z PADA REKSADANA DI KOTA SURAKARTA - Alvira Putri Damayanti; Yuwita Ariessa Pravasanti; Maya Widyana Dewi (CV. Denasya Smart Publisher, 2026)
This study aims to determine the influence of financial literacy, attitude toward risk, and perceived ease of use on Generation Z's investment interest in mutual funds in Surakarta City. This study used a quantitative method with data collection techniques through questionnaires distributed to 100 Generation Z respondents determined using the Cochran formula. Data analysis was performed using multiple linear regression with the help of SPSS version 23 software, which included validity tests, reliability tests, classical assumption tests, F tests, t tests, and the coefficient of determination (R²). The results showed that the three independent variables had a positive and significant influence on investment interest variable. Meanwhile, the t-test results indicate that financial literacy, attitude toward risk, and perceived ease of use each have a positive and significant effect on investment interest, thus all hypotheses in this study are accepted.